Development over time in point-of-care test use in Danish daytime and out-of-hours general practice: a register-based study - Niels Kjær; Malene Plejdrup Hansen; Henrik Schou Pedersen; Morten Bondo Christensen; Linda Huibers (Taylor & Francis Group, 2023)
AbstractObjective To describe the development over time of the use of C-reactive protein (CRP) and rapid streptococcal detection test (RADT) point-of-care tests (POCT) in Danish general practice and to explore associations between patient characteristics and POCT use (i.e. CRP and RADT).Design and settings A register-based study including all general practice clinic consultations in daytime and out-of-hours (OOH) settings in Denmark between 2003 and 2018.Subjects All citizens who had at least one clinic consultation in daytime or OOH general practice within the study period.Main outcome measures We estimated the total and relative use of CRP and RADT POCTs and described the development over time. Crude and adjusted proportion ratios (PRs) were calculated to explore associations between patient characteristics and POCT use.Results Overall, the relative use of CRP POCTs increased. At OOH, a steep increase was noticed around 2012. The relative use of RADT decreased. Patient age 40-59 years and existing comorbidity were significantly associated with a higher use of CRP testing in both settings. A significantly lower use of CRP testing was found for patients with higher educational level. We found a significantly higher use of RADT testing for patients aged 0-19 years and with higher household educational level, whereas comorbidity was associated with a lower use of RADT testing.Conclusion The use of CRP POCT increased over time, whereas the use of RADT POCT decreased. Perhaps the success of implementing CRP as a tool for reducing antibiotic use has reached it limit. Future studies should focus on how and when POCT are used most optimal.Key pointsCRP POC tests and RADT POCTs are frequently used diagnostic tools in general practice, both in daytime and in the out-of-hours setting.There was an increased use of CRP POCTs, particularly in out-of-hours general practice, whereas the use of RADT POCTs declined between 2003 and 2018.CRP POCTs were associated with age of 40-59 years and co-morbidity, while the use of RADT was mostly associated with younger age.